Archetype of globalization: illusory comfort of neo-colonialism in Africa - Joseph Nkang Ogar; Leonard Nwoye; Samuel Akpan Bassey (Center for Humanities and Innovation Studies, 2019)
This paper argues that globalization has been employed to serve the imperialistic interest of the western world. In her drive for hegemony, the west has constantly sought ways of bringing other societies nearer so that domination and exploitation could be total and permanent. Global homogenization is perhaps the most powerful force affecting the Africa landscape today. Global trends such as economic inequality, violent extremism, environmental hazards, changing nature of power are directly related to the practice of neocolonialism. Regrettably, this ongoing homogenization of ethos is more composed of the western liberal capitalism that is most aggressive in neo-colonial pursuits. It is continually shaping not only individuals but also the Africa continent. However, it has its own benefits. However, the negative sides of globalization as a set of policies have exacerbated existing injustice, inhumanity, created, and generated social, economic, political, and cultural inequalities, which should be address. The paper ends by making some recommendations and conclusion.